Involvement of inflammation in normal pregnancy. (18th March 2013) - Palm, Maria; Axelsson, Ove; Wernroth, Lisa; Larsson, Anders; Basu, Samar
Abstract To study the role of inflammation throughout normal pregnancy and postpartum, 37 women with normal pregnancies, including normal neonatal outcome, participated. Blood and urine samples were collected from each woman at least six times during pregnancy and postpartum. Plasma levels of interleukin‐6 (IL‐6) and tumor necrosis factor‐α (TNF‐α) and urinary levels of a prostaglandin‐F2α (PGF2α) metabolite were measured. Median, 25th to 75th centile and average change per gestational week of IL‐6, TNF‐α and the PGF2α metabolite were measured. Levels of IL‐6 increased significantly throughout pregnancy and remained high postpartum. No change in TNF‐α could be seen. The PGF2α metabolite levels increased significantly throughout pregnancy and decreased postpartum. These results suggest that mild but significant inflammatory activity is involved in the development of normal pregnancy, which might have important physiological roles.